2019
DOI: 10.1111/cup.13610
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology‐guided mass spectrometry differentiates benign nevi from malignant melanoma

Abstract: Purpose: Distinguishing benign nevi from malignant melanoma using current histopathological criteria may be very challenging and is one the most difficult areas in dermatopathology. The goal of this study was to identify proteomic differences, which would more reliably differentiate between benign and malignant melanocytic lesions.Methods: We performed histolpathology -guided mass spectrometry (HGMS) profiling analysis on formalin-fixed, paraffin embedded tissue samples to identify differences at the proteomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…The final number of samples enrolled in this study is consistent with similar studies using this technology to classify melanoma. 23,24,28 The panel of dermatopathologists reviewed 16 biconcordant specimens and determined that two samples were unambiguous (included in the 333 triconcordant samples) and 14 were diagnostically challenging and excluded because of lack of consensus. We excluded 22 samples because of assay errors, and six samples did not meet study criteria upon pathological analysis.…”
Section: Pathology Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The final number of samples enrolled in this study is consistent with similar studies using this technology to classify melanoma. 23,24,28 The panel of dermatopathologists reviewed 16 biconcordant specimens and determined that two samples were unambiguous (included in the 333 triconcordant samples) and 14 were diagnostically challenging and excluded because of lack of consensus. We excluded 22 samples because of assay errors, and six samples did not meet study criteria upon pathological analysis.…”
Section: Pathology Analysismentioning
confidence: 99%
“…Previous work demonstrates that this approach can accurately classify various cancers, including head and neck cancers, 20 ovarian cancer, 21 lung cancer, pancreatic cancer, and skin cancer. [22][23][24][25] Previous studies on the skin have shown proof-of-principle to distinguish spitzoid melanoma, 26 malignant melanoma, [27][28][29] and melanoma metastasis. 27,[30][31][32] Original studies used a reagent spotter to perform digestions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Applying a classifier, trained on TMAs, to MALDI MSI measurements of whole sections can be difficult due to technical variations in the measurement process. While a somewhat similar approach has been recently taken to translate a classifier developed on melanoma biopsies to TMAs [13], a successful automatic classification of tissue whole sections from a model developed on TMAs has not been presented yet.…”
Section: Introductionmentioning
confidence: 99%
“…While this is only one study with a small number of test samples, 16 in total, it shows great promise for adaptation to other MSI diagnostic studies. As has been previously shown, standardized sample preparation enables a high degree of reproducibility across both multiple sites [1] and time [5]. The use of robotics for sample preparation and automated image acquisition features such as Bruker's IntelliSlides, as well as streamlined analysis pipelines are helping to make the generation of high‐quality data collection accessible to a broader scientific community, not just to those who have spent years becoming experts in the field.…”
Section: Commentarymentioning
confidence: 99%